Gamma camera calibrations for the Italian multicentre study for lesion dosimetry in 223Ra therapy of bone metastases. (September 2017) - Pacilio, Massimiliano; Cassano, Bartolomeo; Pellegrini, Rosanna; Di Castro, Elisabetta; Zorz, Alessandra; De Vincentis, Giuseppe; Ventroni, Guido; Mango, Lucio; Giancola, Stefano; Ferrari, Mahila; Cremonesi, Marta; Bianchi, Claudia; et al.
Highlights: Gamma camera calibrations for dosimetry in 223 Ra therapy are performed. Eleven gamma cameras of several manufacturers and different models are used. Sensitivity and transmission curves must be measured varying the source size. This study represents a useful compendium to check the obtained calibration data. Abstract: Purpose: The aim was to calibrate gamma cameras in the framework of the Italian multicentre study for lesion dosimetry in 223 Ra therapy of bone metastases. Equipments of several manufacturers and different models were used. Methods: Eleven gamma cameras (3/8- and 5/8-inch crystal) were used, acquiring planar static images with double-peak (82 and 154 keV, 20% wide) and MEGP collimator. The sensitivity was measured in air, varying source-detector distance and source size. Transmission curves were measured, calculating the parameters used for attenuation/scatter correction with the pseudo-extrapolation number method, and assessing their variations with the source size. Results: Values of the calibration factor (geometric mean of both detector sensitivities) ranged from 41.1 to 113.9 cps/MBq. For the smallest source (diameter of 3.5 cm), the calibration factor decrease ranged from −30% to −4%, highlighting the importance of partial volume effects according to the equipment involved. The sensitivity variation with the source-detector distance, with respect to the 15 cm-value, reached 10% (in absolute value) in the range 5–30 cm, but fixing the distance between the two heads, the calibration factor variation with the distance from the midline was within 3.6%. Appreciable variation of the transmission curves with the source size were observed, examining the results obtained with six gamma cameras. Conclusion: Assessments of sensitivity and transmission curve variations with source size should be regularly implemented in calibration procedures. The results of this study represent a useful compendium to check the obtained calibrations for dosimetric purposes.